1997
DOI: 10.1002/(sici)1097-0010(199711)75:3<303::aid-jsfa878>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different types of protein on in vitro availability of intrinsic and extrinsic iron and zinc

Abstract: : The inÑuence of beef, pork and soy proteins on intrinsic and extrinsic iron and zinc in vitro availability was investigated, by measuring mineral dialysability. Intrinsic iron dialysability (percentage of iron dialysed) was similar in the animal proteins and higher than that from soy protein isolate (P \ 0É001). Intrinsic zinc dialysability from pork protein was statistically (P \ 0É001) higher than that from other proteins studied. Beef and soy proteins do not di †er in their percentages of zinc availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Animal proteins increase the bioavailability of non-heme iron, while vegetal proteins decrease its availability (18,19). As has been described in the literature, phytates are strong inhibitors and the formation of diferric and tetraferric phytates in the gastrointestinal tract may decrease the availability of iron for absorption.…”
Section: Discussionsupporting
confidence: 85%
“…Animal proteins increase the bioavailability of non-heme iron, while vegetal proteins decrease its availability (18,19). As has been described in the literature, phytates are strong inhibitors and the formation of diferric and tetraferric phytates in the gastrointestinal tract may decrease the availability of iron for absorption.…”
Section: Discussionsupporting
confidence: 85%
“…In vitro digestion.-The method developed by MILLER et al (10) involving a two-stage (pepsin and pancreatin) digestion was used with minor modifications (12). Amino acid and mineral (calcium, phosphorus, magnesium, iron and zinc) in vitro availability was calculated as the percentage of the element dialysed of the total amount of element present in the aliquot (% dialysability).…”
Section: Methodsmentioning
confidence: 95%
“…Meanwhile, Zn is known to bind both PA and legume oligomeric peptides with strong affinity at near small intestinal pH (∼6.8) ( Zhang et al, 2020 ). Whilst there have been no studies of extrinsically added minerals on the legume protein fractions we have examined to the best of our knowledge, a previous in vitro study on total soy protein found that the addition of Fe or Zn-sulphate at 15 mM (lower than the 20 mM in the current study) led to very little dialyzable quantities of both elements ( Pérez-Llamas et al, 1997 ).…”
Section: Discussionmentioning
confidence: 54%